THE INFLUENCE OF FRENCH LEXICON ON THE ENGLISH LANGUAGE: A STUDY OF BORROWED WORDS AND THEIR PEDAGOGICAL IMPLICATIONS - Dildora Sadriddinova Maxamadjanovna (Western European Studies, 2025)
This article explores the significant influence of the French language on English vocabulary, focusing on the historical context, mechanisms of borrowing, and the implications for English language teaching. By examining key categories of borrowed words, this study highlights their relevance in enhancing vocabulary acquisition and cultural understanding among learners
Keywords: French language; borrowed words; historical context